Partisipasi Pemilih Disabilitas Dalam Pemilihan Kepala Daerah (Pilkada) Kabupaten Kudus Tahun 2018 - Qodarsasi, Umi (Program Studi Tadris IPS Fakultas tarbiyah IAIN Kudus, 2021)
The direct election of regional heads is a new mechanism in democracy in Indonesia where the people in a region directly elect their regional heads. It is hoped that the public will better understand the regional head candidates and choose candidates whose vision and mission is in accordance with regional needs. In the Kudus Regency Regional Election held on June 27, 2018, voter participation in this election was quite significant, amounting to 84.26%. But the disability voter participation is relatively low, that is, only 0,131% from the total of voter. This study aims to identify the lack of disability participation in local elections, forms of disability political participation, and supporting factors disability participation. This research applies descriptive qualitative research method with the political participation of disability analytical framework. The data collection techniques in this qualitative study using primary and secondary data. For primary data, researchers will conduct in-depth interviews of institutions related to the holding of the elections and will also be conducted with disability voters in Kudus Regency, both those registered as Permanent Voter Lists (DPT) and those who have not participated in the elections. As for secondary data, researchers conducted a literature review.